A Rare Case of Scrub Typhus Presenting as Pre Septal Cellulitis - Aishwarya M Angadi; Nagyang Dani; (Col) OK Radhakrishnan; 2nd Year Resident, Department of Ophthalmology, Dr. D. Y. Patil Medical Hospital and Research Centre, Pune, Maharashtra, India. (Journal of Clinical and Diagnostic Research)
Scrub typhus, a vector-borne disease caused by Orientia tsutsugamushi, is known for its diverse clinical manifestations. However, atypical presentations, such as preseptal cellulitis, are rarely documented and pose diagnostic challenges. Hereby, the authors present a case study of a 24-year-old female agricultural worker from a rural area who presented with fever, abdominal pain, vomiting, and facial rashes, along with significant swelling over the right eye since two days. She reported a history of an insect bite on her right upper eyelid. On further examination, an eschar on right upper eyelid, a hallmark of scrub typhus, was noted. Diagnostic tests confirmed scrub typhus with a positive Weil-Felix Test and Immunoglobulin M (IgM) Enzyme-linked Immunosorbent Assay (ELISA). The patient was successfully treated with antibiotics doxycycline, Meropenam and supportive therapies, showing significant improvement. The present case underscores the necessity of considering scrub typhus in the differential diagnosis of preseptal cellulitis, particularly in endemic regions. Recognising atypical presentations is crucial to prevent misdiagnosis and to ensuring timely and appropriate management.